Descriptive study on burden and communication of fatigue among castration-resistant prostate cancer patients in Japan. (4th March 2022) - Iguchi, Taro; Nakamura, Yusuke; Akiyama, Takeshi; Chand, Krishant; Yu, Eric
Abstract: Objective: Prostate cancer is a common malignancy and patients may progress to castration-resistant prostate cancer (CRPC). Among patients with CRPC, fatigue is a common symptom associated with current treatments. The aim of this real-world study was to describe patient-reported fatigue in Japanese patients treated with androgen receptor-axis-targeted therapies for CRPC. Methods: Data of this observational study were collected in a quantitative phase for the description of patient-reported fatigue, and a qualitative phase for elicitation of fatigue perception and barriers to reporting fatigue. Results: In the quantitative phase ( N  = 22), fatigue was investigated in two formats: symptoms report and Brief Fatigue Inventory (BFI). In the report of the symptoms, 12 patients reported tiredness, and four moderate-to-severe tiredness during treatment. In the BFI, all patients reported fatigue; eight reported moderate-to-severe fatigue. The most affected BFI domain was mood: five patients reporting moderate-to-severe impact. In interviews (qualitative phase; N  = 8), diverse patient experience on fatigue was observed, including apathetic feelings, affected speed and distance during the walk, negative impact on profession, housework, or driving, reduced outgoing activity, and difficulty in enjoying time with grandchildren or travel. Five out of eight patients communicated fatigue to their physicians but received diverse reactions. Conclusion: Patient interviews highlighted the impact of fatigue on patients' lives and difficulties in communicating fatigue to physicians. Fatigue frequency after medication may need to be monitored and its burden is considered to provide treatment that meets the needs, wishes, and circumstances of each patient. Further research is needed to elucidate how fatigue affects patients' lives, and underscore patient-physician communication difficulties.